2008
DOI: 10.1111/j.1365-2036.2008.03782.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of using allopurinol co‐therapy as a strategy for overcoming thiopurine hepatotoxicity in treating inflammatory bowel disease

Abstract: SUMMARY BackgroundHepatotoxicity results in the withdrawal of thiopurines drugs, azathioprine (AZA) and mercaptopurine (MP), in up to 10% of patients with inflammatory bowel disease. Our group previously demonstrated that allopurinol with AZA ⁄ ciclosporin ⁄ steroid 'triple therapy' improved renal graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 20 publications
(43 reference statements)
7
96
0
Order By: Relevance
“…Another potential alternative explanation for the decrease in 6-MMPR is that the reduced thiopurine dosage results in suboptimal concentrations for TPMT to function. 36,37 Although we observed a marked effect of allopurinol in 6-TGN formation, it is not clear whether the combination is optimal and if a similar effect would be observed at lower doses of allopurinol. Study of other XO-inhibitors might therefore be of great interest.…”
Section: 29mentioning
confidence: 67%
“…Another potential alternative explanation for the decrease in 6-MMPR is that the reduced thiopurine dosage results in suboptimal concentrations for TPMT to function. 36,37 Although we observed a marked effect of allopurinol in 6-TGN formation, it is not clear whether the combination is optimal and if a similar effect would be observed at lower doses of allopurinol. Study of other XO-inhibitors might therefore be of great interest.…”
Section: 29mentioning
confidence: 67%
“…It has been reported that XO has the potential to generate ROS in human hepatocytes [32] and that the oxidation of 6-MP by XO is involved in the AZA-induced liver injury in patients with inflammatory bowel disease. [33] Another metabolic pathway converts 6-MP into 6-thioinosine monophosphate via hypoxanthine-guanine phosphoribosyl transferase, and this intermediate is then metabolized into active 6-thioguanine nucleotides (6-TGNs). [34] 6-TGNs are also responsible for the cytotoxic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…8 Three further small, retrospective, single-centre studies, including one in a pediatric cohort, have replicated these results, although one viral infectious complication was reported in a total 28 patients. [9][10][11] A summation of the current published retrospective studies shows that combination azathioprine-allopurinol therapy safely and effectively optimizes thiopurine metabolism and achieves the resultant clinical benefits. Prospective studies are underway to further validate the role of combination therapy in otherwise thiopurine-resistant IBD patients.…”
Section: Allopurinol and Azathioprine Combination Therapymentioning
confidence: 99%